Respuesta :
Answer:
x=-3
Step-by-step explanation:
[tex] - 5x + 2(x - 1) = 7[/tex]
[tex] - 5x + 2x - 2 = 7[/tex]
[tex] - 5x + 2x = 7 + 2[/tex]
[tex] - 3x = 9[/tex]
[tex] \frac{ - 3x}{ - 3} = \frac{9}{ - 3} [/tex]
[tex]x = - 3[/tex]
- 5x + 2 ( x - 1 ) = 7
1.) - 5x + 2x - 2 = 7
Distribute 2 into x and - 1.
2.) - 3x - 2 = 7
Add - 5x and 2x together.
3.) - 3x = 9
Add 2 to both sides to keep it even.
4.) x = - 3
Divide both sides again by - 3 to keep it even.
1.) - 5x + 2x - 2 = 7
Distribute 2 into x and - 1.
2.) - 3x - 2 = 7
Add - 5x and 2x together.
3.) - 3x = 9
Add 2 to both sides to keep it even.
4.) x = - 3
Divide both sides again by - 3 to keep it even.